CGIAR GENDER Impact Platform launched at GENDER Science Exchange - Metcalfe, Jenni (CGIAR GENDER Impact Platform, 2022)
Headlining the CGIAR GENDER Science Exchange this week (October 12-14) was the relaunch of the GENDER Platform as a CGIAR Impact Platform, which expands the platform’s mandate beyond gender to include youth and social inclusion.